Measurement properties of the Polish version of the Cystic Fibrosis Questionnaire Revised 14+ in the adult population - Dorota Snop-Perkowska; Jakub Świtalski; Jarosław J. Fedorowski; Anna Augustynowicz (Scientific Reports)
Abstract Measuring the quality of life in patients with cystic fibrosis is an important element of the patient care process. Many tools have been created for this measurement among adults. One of them is the Cystic Fibrosis Questionnaire-Revised 14+ (CFQ-R 14+). Its measurement properties have not been comprehensively assessed in the population of Polish adults. The aim of the study is to verify the construct validity, including structural and criterion validity, as well as internal consistency, of the Polish version of the CFQ-R 14+ in the population of adults with cystic fibrosis. We conducted a cross-sectional survey among adults with cystic fibrosis. After preparing the database, we performed a confirmatory factor analysis (CFA) followed by exploratory factor analysis (EFA) using the parallel analysis method principal axis factoring with Oblimin rotation. Intercorrelations of questionnaire factors and the occurrence of relationships among items for the general scale results was checked. We also presented basic descriptive statistics (mean, median, standard deviation, skewness, kurtosis, minimum and maximum values). The analyses included responses from 220 adult patients. CFA results did not show adequate goodness of fit (χ2(1025) = 2112.35, p < 0.001; CFI = 0.831; TLI = 0.814; RMSEA = 0.069; SRMR = 0.074). After EFA, 6 factors were extracted, considering 40 out of 50 questions of the CFQ-R 14+. CFQ-R 14+ may be useful in assessing the quality of life of Polish adult patients with cystic fibrosis. Our analysis demonstrates that the optimal factor structure of the tool in this population includes 6 scales.